CURRENCY CRISES, SPECULATIVE ATTACKS AND FINANCIAL INSTABILITY IN A GLOBAL WORLD: A POST KEYNESIAN APPROACH WITH REFERENCE TO BRAZILIAN CURRENCY CRISIS. - A Jr., Antonio J.; Ferrari, Fernando; de Paula, Luiz Fernando (Revista Venezolana de Análisis de Coyuntura, 2016)
This paper develops a critical view of the conventional currency crisis models and presents a Post Keynesian view on financial instability and speculative attack. It also analyzes the 1998/1999 Brazilian currency crisis, according to the Post Keynesian approach